Cefmetazole for bacteremia caused by ESBL-producing enterobacteriaceae comparing with carbapenems. Issue 1 (December 2016) - Fukuchi, Takahiko; Iwata, Kentaro; Kobayashi, Saori; Nakamura, Tatsuya; Ohji, Goh
Abstract Background ESBL (Extended spectrum beta-lactamase) producing enterobacteriaceae are challenging organisms with little treatment options. Carbapenems are frequently used, but the emergence of carbapenem resistant enterobacteriaceae is a concerning issue, which may hinder the use of carbapenems. Although cephamycins such as cefoxitin, cefmetazole or cefotetan are effective against ESBL-producersin vitro, there are few clinical data demonstrating effects against bacteremia caused by these organisms. Methods We performed a retrospective observational study on cases of bacteremia caused by ESBL-producers to investigate the efficacy of cefmetazole compared with carbapenems. We also evaluated whether the trend of antibiotic choice changed over years. Results Sixty-nine patients (male 34, age 69.2 ± 14.4), including two relapse cases, were reviewed for this analysis. The most common causative organisms wereEscherichia coli (64, 93 %), followed byKlebsiella pneumoniae andK. oxytoca (2 each, 4 %). The group that received carbapenem therapy (43, 62 %) had increased severity in the Pittsburgh Bacteremic score than the group that received cefmetazole therapy, (1.5 ± 1.5 vs 2.5 ± 2.1, p  = 0.048), while analysis of other factors didn't reveal any statistical differences. Five patients in the carbapenem group and one patient in the cefmetazole group died during the observation period (p  = 0.24). CTX-M-9 were predominant in this series (59 %). Infectious disease physicians initially recommended carbapenems at the beginning of the current research period, which gradually changed over time favoring the use of cefmetazole instead (p  = 0.002). Conclusion Cefmetazole may be safely given to patients with bacteremia caused by ESBL-producers as a definitive therapy, if one can select out relatively stable patients.